Köroğlu, d’Ali Ihsan Kaleci - Erica Letailleur (Carnets)
This paper is a case study about the writing, rehearsals and « video recast » of the play Köroğlu, by the Turkish author and stage director Ali Ihsan Kaleci. Written in 2015, the play has been written simultaneously in French and in Turkish. Then, for the preparation of a video version of the play, he adds to edit several visual elements testifying the preparation and post-production phases. The genealogy of this work in mutation reveals several interwoven lines of work. Here, the process leading to the work, in the complexity of its different steps, is itself a poetic fact. Vivid work, totally integrated to the final creation shown to the audience, it is made with breath, rhythms, readings, and music, which are all elements marking out the artists’ creative journey.